Multicenter observational study on the reliability of the HEART score - Nicola Parenti; Giuseppe Lippi; Maria Letizia Bacchi Reggiani; Antonio Luciani; Mario Cavazza; Antonello Pietrangelo; Alberto Vegetti; Lucio Brugioni; Laura Bonfanti; Gianfranco Cervellin (Clinical and Experimental Emergency Medicine, 2019)
Objective To rapidly and safely identify the risk of developing acute coronary syndrome in patients with chest pain who present to the emergency department, the clinical use of the History, Electrocardiogram, Age, Risk Factors, and Troponin (HEART) scoring has recently been proposed. This study aimed to assess the inter-rater reliability of the HEART score calculated by a large number of Italian emergency physicians. Methods The study was conducted in three academic emergency departments using clinical scenarios obtained from medical records of patients with chest pain. Twenty physicians, who took the HEART score course, independently assigned a score to different clinical scenarios, which were randomly administered to the participants, and data were collected and recorded in a spreadsheet by an independent investigator who was blinded to the study’s aim. Results After applying the exclusion criteria, 53 scenarios were finally included in the analysis. The general inter-rater reliability was good (kappa statistics [κ], 0.63; 95% confidence interval, 0.57 to 0.70), and a good inter-rater agreement for the high- and low-risk classes (HEART score, 7 to 10 and 0 to 3, respectively; κ, 0.60 to 0.73) was observed, whereas a moderate agreement was found for the intermediate-risk class (HEART score, 4 to 6; κ, 0.51). Among the different items of the HEART score, history and electrocardiogram had the worse agreement (κ, 0.37 and 0.42, respectively). Conclusion The HEART score had good inter-rater reliability, particularly among the high- and low-risk classes. The modest agreement for history suggests that major improvements are needed for objectively assessing this component.